Системи опалення на базі відпрацьованих мастил - Поляков, С. П.; Калейніков, Г. Е. (НТУ "ХПІ", 2014)
В работе предложен способ отопления с использованием теплоты процесса комбинированного сжигания в двухфазном потоке водных эмульсий отработанных моторных масел и пиролизного газа. Проведено моделирование процессов горения эмульсий. Подобраны рациональные режимы горения и определен состав пиролизного газа. Установлено, что при определенных соотношениях объемов избыточного воздуха и водяного пара, который испаряется из эмульсии, в составе уходящих газов отсутствуют Н₂ и СО, т. е. наблюдается полное сгорание.

This paper proposes the heating technique for the industrial and residential buildings using the process heat of the combined combustion in the two-phase flow of the water emulsions of waste motor oils and gas, which is formed at high-temperature pyrolysis of oil organic components. The up-to-date methods used for the disposal combustion of low-grade fuels have been analyzed and their disagreement with ecological standards has been established. The mathematical simulation of combustion processes has been carried out. The obtained models allowed for the selection of the rational modes of the combustion behavior of waste oil emulsions and for the determination of pyrolysis gas composition at prescribed process temperature. It has been established that released gases contain no H₂ and CO at certain volume relations of the excess air and water steam that evaporates from the emulsion; it means that the complete combustion of waste oils takes place.
Waste oil-based heating system
Keywords: горіння; емульсії; піроліз; waste oils; combustion; emulsion; pyrolysis